Corporate Leverage, Bankruptcy, and Output Adjustment in Post-Crisis East Asia - Kim, Se-Jik.; Stone, Mark. (Washington, D.C. : International Monetary Fund, 1999)
Different levels of corporate leverage are used in this paper to help explain the wide range of post-crisis output adjustment across East Asia. In the model developed here, highly leveraged firms facing a cutoff of capital inflows are threatened by bankruptcy. These firms respond by eliminating investment and selling their capital goods-at a discount-to try to stay afloat. Lower investment and wasteful capital sales shrink the aggregate capital stock, trigger deflationary pressures, and contract overall output. The available data are broadly consistent with the assumptions and predictions of the model.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet